PEMIDANAAN TERHADAP ANAK DALAM TINDAK PIDANA PERSETUBUHAN TERHADAP ANAK - Halawa, Fikani (LPPM Universitas Nias Raya, 2025)
Conviction is the punishment of a person who has been legally determined and proven guilty of a crime through the criminal justice process. Promiscuity is sexual intercourse between a man and a woman through the insertion of the male's genes into the female's genes. Decision No. 10/Pid.Sus-Anak/2023/PN. Tbt is a decision by a judge who sentences the suspect to prison. Therefore, the purpose of this study is to determine and analyze whether children are punished for sexual crimes against minors. This research collected secondary data, including primary legal data, secondary legal data and third legal data, and used the normative legal research method that uses legal approach, case approach and analysis. Based on the results of the investigations and discussions, it can be concluded that if the offender and the victim are under 18 years of age, the penalty or punishment for minors should be considered in the Juvenile Act for children on 11, 2012. SPPA, they can be prosecuted ​for his crimes. What is he doing? The punishment is imprisonment and job training.